Prescripted living: Gender stereotypes and data-based surveillance in the UK welfare state - Laura Carter (Internet Policy Review, 2021)
The welfare benefits system in the UK has historically favoured individuals who conform to gender stereotypes: it also increasingly uses surveillance and conditionality to determine who is 'deserving' of support. This paper argues that this combination reinforces structures of categorisation and control, risking a vicious cycle which causes harm at both an individual and societal level: it also argues that human rights offers a tool for analysis and resistance to this harm.
Keywords: 300; Data protection; Surveillance; Human rights; gender; Governance